Direct Actions and Archaeology: The Lil’wat Peoples Movement to Protect Archaeological Sites - Angelbeck, Bill; Jones, Johnny (Journal of Contemporary Archaeology, 2019)
Direct action has been a key tactic of many social and political movements throughout history. Here, we consider the relevance of direct actions for archaeology, both for heritage protection and other forms of archaeological activism. We also discuss collaborative and community-based archaeologies as direct relationships and actions that can help prefigure the non-colonial relationships between archaeologists, indigenous peoples, and heritage. In the process, we provide a case history of Lil’wat peoples, who continue to exert control over their unceded territory and heritage from development. In recent decades, the Lil’wat Peoples Movement used direct actions in logging road blockades, to stop developments from damaging and destroying archaeological sites, of which Johnny Jones was a member. We also describe our collaborations over the last decade in investigating sites in various capacities. In so doing, we also consider the parallels between indigenous and anarchist approaches in anarcho-indigenist thought.